Innovation and practice of classroom teaching model with moral education orientation in computer courses - Hou Qinghua; Li Shuai; Li Meirong (ITM Web of Conferences)
This paper centers on the moral education orientation within computer courses and introduces a novel classroom teaching model - the "Situation - based Moral Education - Task - driven - Reflection and Sublimation (SDR)" teaching model. It elaborates on the connotation and implementation procedures of this model, and validates its efficacy in attaining moral education objectives in computer course instruction through specific teaching instances, thereby providing a reference for integrating moral education into computer education. Relevant references are also enumerated.